Stand, landscape and climatic attributes contributing to the probability of Ips typographus damage in Finland - Pulgarín Díaz, John Alexander; Melin, Markus; Mehtätalo, Lauri; Polade, Suraj; Aalto, Juha; Peltola, Heli; Tikkanen, Olli-Pekka (Elsevier, 2026)
Large-scale outbreaks of Ips typographus L. (SBB) have caused extensive damage to Norway spruce (Picea abies (L.) H. Karst.) forests. Under climate change, SBB damage is expected to increase in Northern Europe and especially in Finland, where Norway spruce is one of the most ecologically and economically important tree species. We developed spatially-explicit probability models and SBB damage risk maps using hierarchical logistic regression modelling. We considered various stand, landscape and climatic attributes, including disturbances by routine forestry activities (i.e. new clear-cuts), wind and SBB damage. The analysis drew on detailed, open-access, stand-level forest data collected in 2020–2022 for managed Norway spruce stands in the southern half of Finland (study area), where damage is most prevalent. The study area of 11.4 million ha with more than two million stands Norway spruce stands was split into northern and southern sub-areas to develop sub-area-specific generalised linear mixed effect models for predicting the probability of stand-level SBB damage. We found a generally low probability of SBB damage, higher in the southern sub-area. Landscape attributes showed the strongest effect on SBB damage predisposition, followed by stand and climatic attributes, though the effects differed in sub-areas. The top predictors of SBB damage were proximity to clear-cuts, followed by stand mean diameter at breast height, distance to previous SBB damage and the maximum number of consecutive days with temperature above 25°C. However, careful planning of proactive risk management actions is required, as clear-cuts – including SBB-related salvage loggings – may induce new SBB infestations.
Keywords: salvage logging; forest protection; stand-level risk mapping; boreal forest; forest disturbance